Energy Efficiency : Lessons Learned from Success Stories - Stuggins, Gary (2013)
This study is designed to analyze the energy efficiency policies in seven countries that were successful in achieving low energy intensities or in reducing their energy intensity considerably. The study analyzes the evolution of the energy intensity of these countries from 1990 to 2007, identifying points of inflection in the progress towards improvements. Changes to the policy agenda immediately upstream are explored in an effort to identify cause and affect relationships in energy efficiency improvements. Although direct relationships are difficult to isolate, cross country analyses that point to similar successes among a variety of countries give some confidence that these policies have contributed to reducing energy needs. The energy efficiency of new buildings is relatively easily and in expensively addressed by setting standards: making a new building energy efficient typically adds only 5 percent to the total cost. The purpose of this study is to determine what policy changes make a difference in countries' energy in tensity. The starting point for the analysis was the evolution of countries' energy intensity over time to identify inflection points when notable changes took place. Given that the inflection point could have been caused by external price shocks or structural changes, these causes were analyzed and removed from further consideration. Then changes to the policy agenda during identified periods were explored in an effort to identify cause and affect relationships in energy efficiency improvements.